Bibliometric Analysis of Performance Management: Research Obstacles and Opportunities - Muhammad Hanifa; Bambang Widagdo; Robert Kurniawan (UNIVERSITAS PGRI MADIUN, 2023)
This study presents a bibliometric analysis of publications relevant to performance management. Increased research in management has led to the emergence of a new paradigm in applying performance management systems. The researchers explore how to improve the effectiveness of the performance of companies and institutions. This bibliometric analysis research found 945 articles related to performance management using the Scopus database. The R-Studio bibliometric package is used to conduct data analysis to find trends, worldwide distribution of documents, influential journals, frequently used citations, and countries that dominate publishing articles. This study aimed to analyze articles from the Scopus database related to